Operational and environmental assessment on the use of charcoal in iron ore sinter production - Abreu, Guilherme Correa [UNESP]; Carvalho Júnior, João Andrade de [UNESP]; Silva, Bernardo Enne Correa da; Pedrini, Rinaldo Henrique (Elsevier, 2015)
A study was carried out into the use of charcoal as a supplementary fuel in the iron-ore sintering process. The primary fuel was coke breeze and anthracite with 0, 10, 25, 50 and 100% replacement of the energy input with charcoal to produce sinter. This was achieved by considering the carbon content of each fuel and its corresponding participation on fuel blending, in order to have the same carbon input in each test run. An extensive analysis of the environmental impact was carried out regarding the atmospheric pollutants characterization (dust, sulphur dioxide, nitrogen oxides, carbon monoxide, carbon dioxide, methane, total hydrocarbons, and dioxins and furans). Experimental results indicate that fuel blending where 50% of the heat input was provided by charcoal may be comparable with those using 100% coke, under normal sintering conditions, and may result in a 50% reduction on greenhouse gas emission. It was also observed that while dust, methane and hydrocarbons emissions increased, the total dioxins and furans, expressed as polychlorinated dibenzodioxins/furans, decreased approximately 50% when compared with operation with 100% coke.
Keywords: Sintering; Iron ore; Charcoal; Environmental impact